“Nature defeated by man gives rise to gods”: Eco-spirituality in the Ecological Thought of Luis Oyarzún - Donoso Aceituno, Arnaldo Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper reflects on the links between ecological thought and spirituality in the writing of the Chilean intellectual Luis Oyarzún (1920-1972). His prose discloses the tensions between spiritual and secular in a context of environmental crisis. I propose the term eco-spirituality to describe the assemblage of the domains of ecological and spiritual. Oyarzún’s persona understands material nature as sacred and the human being as a custodian or a minuscule part that can merge with the whole. I examine two practices thematized in Oyarzún’s writing, pilgrimage and silence, consummations of his eco-spiritual experience.